2015
DOI: 10.1093/carcin/bgv078
|View full text |Cite
|
Sign up to set email alerts
|

Repair synthesis step involving ERCC1-XPF participates in DNA repair of the Top1-DNA damage complex

Abstract: Topoisomerase 1 (Top1) is the intercellular target of camptothecins (CPTs). CPT blocks DNA religation in the Top1-DNA complex and induces Top1-attached nick DNA lesions. In this study, we demonstrate that excision repair cross complementing 1 protein-xeroderma pigmentosum group F (ERCC1-XPF) endonuclease and replication protein A (RPA) participate in the repair of Top1-attached nick DNA lesions together with other nucleotide excision repair (NER) factors. ERCC1-XPF shows nuclease activity in the presence of RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…These data together hint at a role for FEN1 in a FA-related pathway. This is somewhat consistent with previous data as FEN1 activity has been shown to be stimulated by the FA core-complex member FANCA [93], and has been shown to be involved in replication fork processing and restart [15, 94]. Collectively, our data suggest that FEN1 inhibition results in accumulation of DNA damage, which requires the FA pathway for repair.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These data together hint at a role for FEN1 in a FA-related pathway. This is somewhat consistent with previous data as FEN1 activity has been shown to be stimulated by the FA core-complex member FANCA [93], and has been shown to be involved in replication fork processing and restart [15, 94]. Collectively, our data suggest that FEN1 inhibition results in accumulation of DNA damage, which requires the FA pathway for repair.…”
Section: Resultssupporting
confidence: 93%
“…This suggests a role for FEN1 in replication-coupled DNA repair, which could include damage induced by FEN1 inhibition. The role for FEN1 in the repair of these lesions is unclear, however there is evidence to suggest that FEN1 plays a role in replication restart and the processing of stalled replication forks [15, 16, 94, 98]. It would be interesting to determine the precise function of FEN1 in this pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide excision repair facilitates the recognition of DNA damage, via activation of XPC, with repair of the DNA lesions and elimination of CPDs in the helix by the ERCC1 exonuclease (Maytin et al, 1993;Rass and Reichrath, 2008;Rocca et al, 2010;Takahata et al, 2015;van Steeg and Kraemer, 1999). In our study, significant downregulation of XPC, a fundamental DNA damage surveillance protein (Cheo et al, 1996;Pines et al, 2009), and ERCC1, an exonuclease that facilitates removal of DNA lesions (Nagai et al, 1995;Yang et al, 2007), was observed in UVB plus heat treated keratinocytes.…”
Section: Uvb Plus Heat Dna Damage Repair and Cell Survivalsupporting
confidence: 57%
“…ERCC1 protein XPF and ERCC4 can recognize damaged DNA 5′-end and function as 5′–3′ endonuclease of nucleic acids, thereby reducing the possibility of structural chromosome aberrations and guarantying genomic instability 26. Recently, an epidemiological study suggested that inhibition of expression of ERCC1 played an essential role in reducing the ability of DDP–DNA adduct repair, after which the tumor incidence increased with low resistance in drugs 27. Furthermore, Ma et al28 reported that the ERCC1 rs11615 polymorphism contributed to the clinical outcomes of patients with gastrointestinal cancer, such as gastric cancer and colorectal cancer who were treated by oxaliplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%